If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = -30x + 10 Reorder the terms: 10 = 10 + -30x Add '-10' to each side of the equation. 10 + -10 = 10 + -10 + -30x Combine like terms: 10 + -10 = 0 0 = 10 + -10 + -30x Combine like terms: 10 + -10 = 0 0 = 0 + -30x 0 = -30x Solving 0 = -30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30x' to each side of the equation. 0 + 30x = -30x + 30x Remove the zero: 30x = -30x + 30x Combine like terms: -30x + 30x = 0 30x = 0 Divide each side by '30'. x = 0 Simplifying x = 0
| (w)=0 | | .25(12+x)=.6+.35x | | 9p^2-12p=0 | | (w)=1 | | (w)=-1 | | -9n^2-9=315 | | 5+6x+25=180 | | (w)=-2 | | 8-10p=88 | | 4c-10=-9+3c | | (7y+2)(y-5)= | | 8x(8+6x)=20 | | .25(12x)=.6+.35x | | -2(x-4)=-6(2+x) | | 5(x+1)+51=-2x | | 4x+14=6x-26 | | 2m+7(m-1)=-21-5m | | 5+6y=5y+10 | | -abx^2+bcx+1=0 | | 5+y^2+7=3 | | 15w-22=-111 | | 8v+4=2v-8 | | 4(x-4)+2x=4x-6 | | (6y+5)(y-2)= | | 13x+7=6x+14 | | -3+7q=-7+9q | | -(1+6m)+6m=-11+3(r-7) | | Y=(5t^2)*(5t^3) | | -2(3)(-5)= | | 3(7-4x)=-39 | | 12=96 | | 3x+3+55=180 |